2011
DOI: 10.1007/s12687-011-0055-z
|View full text |Cite
|
Sign up to set email alerts
|

Tracking clinical genetic services for newborns identified through newborn dried bloodspot screening in the United States—lessons learned

Abstract: To determine how US newborn dried bloodspot screening (NDBS) programs obtain patient-level data on clinical genetic counseling services offered to families of newborns identified through newborn NDBS and the extent to which newborns and their families receive these services. These data should serve to inform programs and lead to improved NDBS follow-up services. Collaborations were established with three state NDBS programs that reported systematically tracking genetic counseling services to newborns and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Genetic counseling is essential for family understanding, knowledge, satisfaction, and compliance (Bjorvatn et al, 2007; Rutherford, Zhang, Atzinger, Ruschman, & Myers, 2014). Similar rates of genetic counseling were found by Livingston et al in 2011 when they studied rates of genetic counseling for metabolic disorders tracked by newborn screening programs in Minnesota, Missouri, and Rhode Island (Livingston et al, 2011). This is in stark contrast to recent data reported from the ABOUT study where this group investigated the rate of genetic counseling for women undergoing BRCA genetic testing, and found that only 36.8% of received genetic counseling (Armstrong et al, 2015).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Genetic counseling is essential for family understanding, knowledge, satisfaction, and compliance (Bjorvatn et al, 2007; Rutherford, Zhang, Atzinger, Ruschman, & Myers, 2014). Similar rates of genetic counseling were found by Livingston et al in 2011 when they studied rates of genetic counseling for metabolic disorders tracked by newborn screening programs in Minnesota, Missouri, and Rhode Island (Livingston et al, 2011). This is in stark contrast to recent data reported from the ABOUT study where this group investigated the rate of genetic counseling for women undergoing BRCA genetic testing, and found that only 36.8% of received genetic counseling (Armstrong et al, 2015).…”
Section: Discussionsupporting
confidence: 70%
“…This is in stark contrast to recent data reported from the ABOUT study where this group investigated the rate of genetic counseling for women undergoing BRCA genetic testing, and found that only 36.8% of received genetic counseling (Armstrong et al, 2015). Evidence suggests that genetic counseling is provided more frequently in clinics providing care for inherited metabolic conditions than in other fields of genetics (Hinton et al, 2014; Livingston et al, 2011). This may be because patients with rare inherited metabolic disorders are seen regularly by specialist providers for routine follow-up, often at academic medical centers, while other genetic testing (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for families of newborns identified through the respective state's dried blood spot screening, there are limited published reports about the numbers of encounters with genetic service providers. 22 …”
Section: Discussionmentioning
confidence: 99%
“…reported that the Ministry of Health, laboratories, hospitals, health houses, legislator organisations and insurance companies should be involved in the process of newborn screening. In another study, Livingston et al 43. noted that data obtained from tracking newborn clinical genetic services are important for improving newborn screening programmes, and cooperation between genetic services and organisations which are responsible for implementing newborn screening programmes is necessary.…”
Section: Discussionmentioning
confidence: 99%